Theorizing the avant-garde : modernism, expressionism, and the problem of postmodernity - Murphy, Richard (Richard John) (Literature, culture, theory, 1999)
In Theorizing the Avant-Garde: Modernism, Expressionism, and the Problem of Postmodernity, Richard Murphy mobilizes theories of the postmodern to challenge our understanding of the avant-garde. He assesses the importance of the avant-garde for contemporary culture and for the debates among theorists of postmodernism such as Jameson, Eagleton, Lyotard and Habermas. Murphy reconsiders the classic formulation of the avant-garde in Lukacs, Bloch and Burger, especially their discussion of aesthetic autonomy, and investigates the relationship between art and politics via a discussion of Marcuse, Adorno and Benjamin.